1990
DOI: 10.1007/bf00027499
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and sequence analysis of two seed-expressed acyl carrier protein genes from Brassica napus

Abstract: Genomic Southern blot analysis of Brassica napus DNA indicates that seed-expressed acyl carrier protein (ACP) is encoded by a multigene family of some 35 genes/haploid genome. Two genomic clones encoding B. napus ACP have been isolated and sequenced. The coding sequences of the 2 respective genes were found to be perfectly homologous to 2 distinct B. napus seed-expressed cDNAs and therefore represent seed-expressed forms of ACP. The 2 genomic ACP sequences share 94% homology within their coding sequences. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Southern blotting has confirmed that the oleosin gene under study is part of a multigene family with up to six loci per haploid genome. This gene multiplication is common to many embryo-specific genes [7,34,3] in B. ncO)us and may be a general mechanism for rapidly accumulating seed storage products in response to highly variable conditions within the developing seed. Southern blotting was also utilised to demonstrate that the previously reported cDNA is transcribed from the presented oleosin gene.…”
Section: Discussionmentioning
confidence: 99%
“…Southern blotting has confirmed that the oleosin gene under study is part of a multigene family with up to six loci per haploid genome. This gene multiplication is common to many embryo-specific genes [7,34,3] in B. ncO)us and may be a general mechanism for rapidly accumulating seed storage products in response to highly variable conditions within the developing seed. Southern blotting was also utilised to demonstrate that the previously reported cDNA is transcribed from the presented oleosin gene.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that plastids represent the major site of de novo fatty acid synthesis (9,30). Acyl carrier protein is located in chloroplasts (31), and their cloned genes have a transit peptide sequence to enter into the plastid (32,33). The fatty acid synthetase is a dissociable type II enzyme, which is analogous to that of Escherichia coli and is located in plastids (9).…”
Section: Resultsmentioning
confidence: 99%
“…Confirmation that rape thioesterase is indeed encoded by a multigene family was provided by Southern analysis of genomic DNA which suggested 8-10 gene copies. Previous studies on another fatty acid synthase (FAS) component from oil seed rape, acyl carrier protein, showed it to be encoded by a heterogeneous multigene family of some 35 members [6]. The observed heterogeneity may reflect the allotetra- Fig.…”
Section: N L 2 a A A G T T G T A T G C A A T G T A A T A C T T T T T mentioning
confidence: 99%